Sistem Informasi Pariwisata Di Kabupaten Lospalos Berbasis Web - Julio Monteiro Da Costa; Mochamad Mizanul Achlaq (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
One of the excellent tours in Timor Leste is a tourist attraction on Jaco Island including Com Beach, Ili Kerekere Cave, Pouzada Tutuala and Lake Iralalaro, as well as unspoiled natural scenery, traditional houses as well as icons of the city of Lospalos which are in demand by local and foreign tourists, which are can offer unique views and beaches with the clearest water. The formulation of the problem used in this research is how to design a tourist information system website in the Lospalos district easily and quickly accessed and how to implement tourism promotion on the website. The research method uses descriptive qualitative research methods and the application of the waterfall model, where this method has several stages, namely analysis, design, coding, and testing. When creating this information system, two types of use case diagrams were created, namely user and admin, for system admins for further information. In the user view, the user enters the homepage, sees the homepage, sees popular tours, displays the results, the homepage, the user enters the profile, sees the profile, the user enters the tour, sees the tour, displays the results, the contact user displays WhatsApp and Email. the system can contain information about tourism in Lospalos Regency, so that it can make it easier for tourists to access information related to tourist attractions in Lospalos district and the designed system provides images of information on tourism in Lospalos district and visitors can view tourist profiles and contacts. It is hoped that for the next development it can be used on mobile so that it can make it easier for users and also develop the website by adding hotels and even airplane or ship tickets and also entry tickets to tourist attractions in Lospalos district.